2017
DOI: 10.14256/jce.1860.2016
|View full text |Cite
|
Sign up to set email alerts
|

Physicomechanical properties of fly ash applicable in road construction

Abstract: Physico-mechanical properties of fly ash applicable in road constructionAn experimental research of physico-mechanical properties of fly ash and ash stabilized with lime and cement, as used in road construction, is presented in the paper. The binder was added in the proportion of 2, 4 and 6 % of the total quantity of fly ash. The testing revealed that ash samples with and without binder can be used for improvement of foundation soil and for construction of embankments and subgrade layers, but are not recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…To protect the ecological environment and lower road construction cost, researchers are currently exploring use of industrial waste as a substitute for traditional cement and lime. For example, Mavroulidou [21] explored approaches to improve different clay properties of waste paper sludge [21], while Seslija et al [22] used fly ash to replace natural materials as building materials. On the other hand, Etim et al [16] used iron ore tailings and lime as soil conditioners to improve the properties of black cotton soil.…”
Section: Introductionmentioning
confidence: 99%
“…To protect the ecological environment and lower road construction cost, researchers are currently exploring use of industrial waste as a substitute for traditional cement and lime. For example, Mavroulidou [21] explored approaches to improve different clay properties of waste paper sludge [21], while Seslija et al [22] used fly ash to replace natural materials as building materials. On the other hand, Etim et al [16] used iron ore tailings and lime as soil conditioners to improve the properties of black cotton soil.…”
Section: Introductionmentioning
confidence: 99%
“…After the tests, it is concluded that the ash can be used to improve the pavement base. Some of the authors have examined the use of ash as a material for the construction of road embankments using a hydraulic binder (lime and cement) with different percentages [2]. The authors came to the conclusion that the application of ash with or without binders can be used for road construction and give quite good test results.…”
Section: Introductionmentioning
confidence: 99%